Maternal infection in pregnancy and childhood leukaemia: a systematic review and meta-analysis - He, J-R; Ramakrishnan, R; Hirst, JE; Bonaventure, A; Francis, SS; Paltiel, O; Håberg, SE; Lemeshow, S; Olsen, S; Tikellis, G; Magnus, P; Murphy, MFG; et al. (Elsevier, 2019)
Objective To summarize the published evidence regarding the association between maternal infection during pregnancy and childhood leukemia.